Penyusunan peta sastra melalui penelusuran jejak sastra Indonesia sebagai identitas bangsa yang berkarakter - Sulaiman Sulaiman; Priyono Tri Febrianto (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This research departs from various issues related to the definition of literature which always raises debates and dissatisfaction with the existing definition. Literature as national identity also raises debates. Those two reasons had, directly and indirectly, influenced the development of Indonesian map literature. Formation of Indonesian map literature from different periods needed to be clarified so it could provide a clear definition of Indonesian literature development. The aims of this research are (1) constructing Indonesian literature map which explains the development of Indonesian literacy from different periods; and (2) explaining literature as nation identity with character. To analyze the issues, theories and concepts about literature are applied. Thisresearch uses descriptive method. Data gathered by descriptive technique and content analysis. The main finding of this research is that there is a significant influence of Indonesian literature development by tracing Indonesian literature to the formation of nation identity with character.